2008
DOI: 10.1016/j.neuropharm.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of AMPA receptors in the antidepressant-like effects of lithium in the mouse tail suspension test and forced swim test

Abstract: In addition to its clinical antimanic effects, lithium also has efficacy in the treatment of depression. However, the mechanism by which lithium exerts its antidepressant effects is unclear. Our objective was to further characterize the effects of peripheral and central administration of lithium in mouse models of antidepressant efficacy as well as to investigate the role of alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptors in these behaviors. We utilized the mouse forced swim test (FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 75 publications
7
69
2
Order By: Relevance
“…However, several other mechanisms to account for the action of lithium have been proposed including inositol depletion, indirect activation of AKT, and inhibition of a β-arrestin/ AKT signaling complex (15,23,(48)(49)(50). Behavioral tests such as locomotion, tail-suspension test (TST), forced swim test (FST), and dark-light emergence test in mice are sensitive to lithium treatment (51,52). Previous work from our laboratory has shown that global βarr2 (βarr2 −/− ) or heterozygous GSK3β genetic deletion (GSK3β +/− ) or systemic pharmacological inhibition of GSK3β reduces DA-dependent hyperlocomotion, immobility time in the tail-suspension test as well as the latency to cross in the dark-light emergence test, thereby phenocopying the effects of lithium.…”
Section: Discussionmentioning
confidence: 99%
“…However, several other mechanisms to account for the action of lithium have been proposed including inositol depletion, indirect activation of AKT, and inhibition of a β-arrestin/ AKT signaling complex (15,23,(48)(49)(50). Behavioral tests such as locomotion, tail-suspension test (TST), forced swim test (FST), and dark-light emergence test in mice are sensitive to lithium treatment (51,52). Previous work from our laboratory has shown that global βarr2 (βarr2 −/− ) or heterozygous GSK3β genetic deletion (GSK3β +/− ) or systemic pharmacological inhibition of GSK3β reduces DA-dependent hyperlocomotion, immobility time in the tail-suspension test as well as the latency to cross in the dark-light emergence test, thereby phenocopying the effects of lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral Tests. The forced swim test (FST) and tail suspension test (TST) were conducted as previously described (24). The immobility time was applied as the indicator for behavioral despair.…”
Section: Methodsmentioning
confidence: 99%
“…Post hoc analysis revealed a significant effect of GE extract alone compared to each of the other 2 groups (both, p<.05), and no other significant differences. We omitted the group treated by DW and NBQX, because, for both the FST and TST there was no significant effect of NBQX alone to change immobility time compared to vehicle treated mice in previous studies 28,30,57,58) .…”
Section: Antidepressant-like Effects Of Ge Extract In the Tstmentioning
confidence: 99%